SDG 3 landscape in low and Middle Income Countries (LMIC) and implementation challenges - Sharifa Ezat Wan Puteh,; Umar Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Seventeen Sustainable Development Goals (SDGs) presents opportunities for inclusive and resilient development pursuits. This article assessed SDG 3 landscape in the context of Low and Middle Income Countries (LMIC). SDG 3 focus on healthy lives and inclusive well-being, it has 13 targets. Health settings in LMIC are donor influence, in which cardinal issues are often ignored, concentrating on donor’s priorities, a situation befitting who paid the piper dictate the tune dictum. The paper explored SDG 3 related issues and implementation challenges that looms over the LMIC, by analysing the SDG 3 components’ strength, opportunities, and threats focusing on Sub-Sahara Africa (SSA). The study utilised desk literature survey approach, using defined key search terms to searched databases, applying diverse combinations covering diseases, research and policy themes, from which 235 papers were retrieved and checked for further review. The challenges confronting SDGs implementation in SSA are numerous; for example, 89% of the SSA are at risk of developing malaria; in 2014, 57.3 million children were stunted; progress was overshadowed by population growth and 40% lives in abject poverty, with 23% of undernutrition status. These gaps highlight poor governance, an implementation challenge that need to be address. SDG 3 implementation strength lies with policy makers and bureaucrats, while its weakness depicts logistical, accountability and coordination deficits that requires stakeholders’ rapport through collaborations. Successful implementation of the SDG 3 calls for trans-disciplinary collaborations and coordination in the shape of Public Private Partnership (PPPs), for inform policies that transform theory into action.